Level of depression among Wives of alcoholics and Wives of Non-alcoholics - N. Akila,; Dr. S. Jeyalakshmi,; Dr. P. Therese, (The Bioscan, 2024)
The level of depression among the wives of alcoholics and non-alcoholics affects their daily routine and they are affected both physically and psychologically. The main objective of the study is to assess the level of depression and compare the level of depression among wives of alcoholics and wives of non-alcoholics. A community-based comparative study was conducted among 25 wives of alcoholics and 25 wives of non-alcoholics at a selected village in Tamil Nadu. Samples were selected by the nonprobability purposive sampling technique. Data were collected to assess the level of depression by Beck depression inventory. Collected data were analyzed by using descriptive and inferential statistics. The study shows that among wives of alcoholics, the majority 9 (36%) had moderate levels of depression and the majority of wives of non-alcoholics 15 (60%) were normal. The study concluded that the level of depression among wives of alcoholics was higher compared to wives of non-alcoholics.